Alpha-Synuclein in the Regulation of Brain Endothelial and Perivascular Cells: Gaps and Future Perspectives - Bogale, Tizibt Ashine; Faustini, Gaia; Longhena, Francesca; Mitola, Stefania; Pizzi, Marina; Bellucci, Arianna (Frontiers in Immunology, 2021)
Misfolded proteins, inflammation and vascular alterations are common pathological hallmarks of neurodegenerative diseases. Alpha-synuclein is a small synaptic protein that was identified as a major component of Lewy bodies and Lewy neurites in the brain of patients affected by Parkinson’s disease (PD), Lewy body dementia (LBD) and other synucleinopathies. It is mainly involved in the regulation of synaptic vesicle trafficking but can also control mitochondrial/endoplamic reticulum (ER) homeostasis, lysosome/phagosome function and cytoskeleton organization. Recent evidence supports that pathological forms of α-synuclein can also reduce the release of vasoactive and inflammatory mediators from endothelial cells (ECs) and modulates the expression of tight junction (TJ) proteins important for maintaining blood brain barrier (BBB). This hints that α-synuclein deposition can affect BBB integrity. Border associated macrophages (BAMs) are brain resident macrophages found in association with the vasculature (PVMs), meninges (MAMs) and choroid plexus (CPMs). Recent findings indicate that these cells play distinct roles in stroke and neurodegenerative disorders. Although many studies have addressed how α-synuclein may modulate microglia, its effect on BAMs has been scarcely investigated. This review aims at summarizing the main findings supporting how α-synuclein can affect ECs and/or BAMs function as well as their interplay and effect on other cells in the brain perivascular environment in physiological and pathological conditions. Gaps of knowledge and new perspectives on how this protein can contribute to neurodegeneration by inducing BBB homeostatic changes in different neurological conditions are highlighted.